Antifungal Efficacy of Amphotericin B in Candida Albicans Endocarditis Therapy: Systematic Review - Bezerra, Lucas Soares; Silva, Janielli Assis da; Santos-Veloso, Marcelo Antônio Oliveira; Lima, Sandro Gonçalves de; Chaves-Markman, Ândrea Virgínia; Jucá, Moacir Batista (Revista brasileira de cirurgia cardiovascular, 2020)
Although it is the most common agent among the fungal causes of endocarditis, Candida albicans endocarditis is rare. To evaluate the efficacy of amphotericin B in the treatment of C. albicans endocarditis beyond a systematic review. Articles in English, Spanish and Portuguese, conducted in the following databases: MEDLINE, LILACS, IBECS and SciELO, in humans and published in the last 25 years. Observational studies, clinical trials, and case series providing data on the amphotericin B use in patients with a C. albicans endocarditis diagnosis without age limitations. From the initial search (n=79), 25 articles were fully evaluated, of which 19 were excluded for meeting one or more exclusion criteria, remaining five articles (two observational studies and three case series). Patients using amphotericin B demonstrated improvement in survival rates, and its main use was in association with the surgical method as well as with caspofungin association. Literature lacks evidence to conclude about efficacy and safety of amphotericin B in the treatment of fungal endocarditis. Randomized clinical trials are necessary to provide better evidence on the subject.